Pengaruh Senam Diabetik terhadap Sensitivitas Kaki (Ulkus) dan Kadar Gula Darah Penderita Diabetes Melitus Tipe II - Aina Nurus Sofa; Alfiah Rahmawati (Jurnal Health Sains, 2021)
In Indonesia the incidence of diabetes mellitus continues to increase. Complications of diabetes occur in all organs of the body with a 50% cause of death due to coronary heart disease and 30% due to kidney failure. Besides death, diabetes also causes disability. As many as 30% of diabetics overcome the complications of retinopathy and 10% overcome foot amputations due to diabetic ulcers. Diabetes mellitus is a disease characterized by evolution caused by differences in insulin production or impaired insulin performance or because of both. Management of diabetes mellitus through the five main pillars, one of which is diabetic exercise. Diabetic gymnastics is a form of aerobic physical exercise for diabetics with movements that have been deliberately chosen to follow the rhythm of the chosen music that requires the provision of rhythmic, continuity and a certain duration to achieve the expected goals. This gymnastics suggests 3-5 times / week. The aim is to determine the sensitivity of the feet of people with diabetes mellitus, the difference in blood sugar levels before and after formulation in patients with Type II DM. This search article is based on data such as Google Scholar. The key words are "diabetes exercise", "foot sensitivity", "blood glucose levels", "type II diabetes patients" and the authors found 5 relevant articles from 2014-2020. This article is expected to be an additional information to keep scheduling diabetic gymnastics regularly and continuously